Various Components With The Properties To Reduce The Flammability Of Polymer Materials - Khozhakulov Zhurabek Ergashovich (Academia One, 2024)
This scientific article is devoted to the study of various components that have the properties of reducing the flammability of polymer materials. The work analyzes existing methods for reducing the flammability of polymers and proposes new approaches to the use of components that help improve the fire safety of materials. The research represents an important contribution to the field of materials safety and can be used in the development of new fire-resistant polymer materials
Keywords: components; polymer material; products